Comparison of the Effectiveness of Self-Compassion-Focused Therapy and Stress Inoculation Training on Perceived Stress among Parents of Children with Cancer - Salehi, Shadi; Taheri, Afsaneh; Lotfi Kashani, Farah (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to compare the effectiveness of Self-Compassion-Focused Therapy (SCFT) and Stress Inoculation Training (SIT) on perceived stress among parents of children with cancer. This study employed a quasi-experimental design with a pretest–posttest control group and a two-month follow-up assessment. The statistical population consisted of parents of children with cancer who attended medical and psychological treatment centers in Tehran in 2026. Among them, 45 participants were selected through convenience sampling based on the study inclusion criteria and were randomly assigned to three groups of 15 participants each (two experimental groups and one control group). Data were collected using the Perceived Stress Scale (PSS) developed by Cohen et al. (1983). The therapeutic interventions included the implementation of the Self-Compassion-Focused Therapy protocol based on Gilbert’s treatment program (2012) and Stress Inoculation Training based on Meichenbaum’s psychological inoculation program (Mobini, 2007). Each intervention was administered in a group format over 10 weekly sessions for the experimental groups. The control group received no intervention during the study period. Data were analyzed using descriptive statistics and mixed-design repeated-measures analysis of variance. The results indicated that both Self-Compassion-Focused Therapy and Stress Inoculation Training significantly reduced perceived stress among parents of children with cancer, and the therapeutic effects remained stable at the follow-up assessment (p < .05). Furthermore, the comparison of the two interventions demonstrated that Stress Inoculation Training was more effective than Self-Compassion-Focused Therapy in reducing perceived stress. The findings suggest that both therapeutic approaches can be utilized as effective psychological interventions to improve the mental health of parents of children with cancer.